Al-Wala’ wal Bara’: Loyalty, Identity, and the Prophet’s Message through the Lens of Hadith Criticism - Halimatus Sa'diyah; Amrulloh Amrulloh (JOURNAL OF QUR'AN AND HADITH STUDIES, 2025)
This research analyzes the hadith narrated by Imam Abu Daud, number 4681, concerning the concept of al-Wala' wal-Bara', a crucial pillar in understanding Muslim social relations and creed, as it is often misinterpreted leading to exclusive or even extremist attitudes towards non-Muslims. Employing a descriptive qualitative method and library research, the analysis involves an external approach (hadith takhrij, jarh wa ta'dil, i'tibar sanad, and matan criticism) and an internal approach (textual understanding from hadith commentaries and contextual understanding based on contemporary thought, especially Sheikh Yusuf al-Qaradawi's approach). The findings indicate that the hadith is graded hasan in both its chain of narration (sanad) and text (matan). Substantively, it teaches that love and hate for the sake of Allah signify perfect faith. This study concludes that al-Wala' wal-Bara' must be understood in a balanced way to avoid misuse to justify intolerance. The research also highlights the clear distinction between loyalty (al-wala'), a matter of creed, and tolerance, a social principle. Loyalty to Allah and His religion does not negate fair and good treatment of non-Muslims, provided they are not hostile to Islam. The implication is the importance of a moderate approach in understanding hadiths related to interfaith relations so that Islamic values of rahmatan lil 'alamin (mercy to all worlds) can be realized in social practice.